Effect of post-processing methods on the surface quality of Ti6Al4V fabricated by laser powder bed fusion - Lu, Dong; Liu, Zhenyu; Wei, Xiongmian; Chen, Chen; Wang, Di (Frontiers in Materials, 2023)
This work investigated the effect of post-processing methods (i.e., sandblasting, electrolytic polishing, chemical polishing, and abrasive flow polishing) on the surface quality of Ti6Al4V fabricated by laser powder bed fusion (LPBF) additive manufacturing. The changes in surface roughness and morphology of the 45° inclined square and curved pipe Ti6Al4V samples processed with post-processing were observed, and the weight and elemental changes of the parts were also analyzed. The result reveals that sandblasting, electrolytic polishing, chemical polishing, and abrasive flow polishing are all effective in improving the surface quality of Ti6Al4V parts fabricated by LPBF. The effect of sandblasting is mainly caused by sharp-edged grit driven by high-speed airflow, resulting in the lowest surface roughness and the least influence on the weight, but may contaminate the surface with residual brown corundum. Electrolytic polishing and chemical polishing achieve surface quality improvement through different corrosion patterns without changing the surface composition. The surface smoothness of parts processed with chemical polishing is the best, while the weight loss rate of the sample processed with electrolytic polishing is the most at about 7.47%. Abrasive flow polishing presents a remarkable effect on polishing the internal surface of the Ti6Al4V sample by the extrusion scratching, extrusion deformation, and micro-cutting effects of abrasive on the surface. The findings can provide important engineering references for the post-processing of precision Ti6Al4V parts fabricated by LPBF and further promote the engineering applications of Ti6Al4V parts.